A systematic revision of the Australian ploiarioline thread-legged assassin bugs (Hemiptera: Reduviidae: Emesinae) - Tatarnic, Nikolai J.; Wall, Michael A.; Cassis, Gerasimos (Zootaxa, 2011)
The Australian members of the emesine tribe Ploiaiolini (Hemiptera: Heteroptera: Reduviidae) are revised. A key, as well as diagnoses and figures, are presented for all 16 Australian species. Seven new species are described. Four species previously not recorded from Australia are included in the continent’s fauna. Emesopsis is expanded to include species in which the basal cell of the forewing is absent.